A Novel Approach to Cyber Hazard Management Intelligence System - Bala Bharathi, B; Suresh Babu, E (International Journal of Engineering and Technology, 2018)
Detecting and defending against insider and outsider threats seems to be a major challenge for information security system. such that cyber-attacks pose a silent threat for a company with a havoc likely to be in billions, besides slaughtering investor confidence and denting brand image. Long-established and ongoing solutions target mainly to assimilate many known threats in the form of consistent information such as logical & physical address, etc. into detection and blocking techniques. Our proposed solution elongates forward by using Cyber threat intelligence (CTI) which is used to inform decisions timely regarding subject response to the menance or hazard, where the vulnerable systems are identified using honeypot, through integration of logs for detecting network, host intrusions using SIEM technology which would efficiently manage the occurrence of threat by using cyber hazard management to mitigate the cyber threat actions, fortify incident response efforts and enhance your overall security posture.Â Â